Impact of Escherichia coli probiotic strains ED1a and Nissle 1917 on the excretion and gut carriage of extended-spectrum beta-lactamase-producing E. coli in pigs. (December 2021) - Mourand, Gwénaëlle; Paboeuf, Frédéric; Grippon, Pauline; Lucas, Pierrick; Bougeard, Stéphanie; Denamur, Erick; Kempf, Isabelle
Highlights: The inoculated cefotaxime-resistant E. coli was a good pig gut colonizer. Probiotics could not reduce faecal excretion of resistant E. coli in inoculated pigs. Resistant E. coli titers were lower in digestive tracts of the probiotic-treated pigs. No transfer of the bla CTX−M-1 gene was detected. Abstract: We evaluated the impact of the administration of two Escherichia coli probiotic strains (ED1a and Nissle 1917) to pigs on the gut carriage or shedding of extended-spectrum beta-lactamase-producing E. coli . The probiotics were given to four sows from 12 days before farrowing to the weaning day, and to the 23 piglets (infected treated group (IPro)) from birth to the age of 49 days. Four other sows and their 24 piglets (infected non-treated group (INT)) did not receive the probiotics. IPro and INT piglets ( n  = 47) were orally inoculated with the strain E. coli 17–348F-RifR carrying the bla CTX−M-1 gene and resistant to rifampicin. Cefotaxime-resistant (CTX R ) E. coli and rifampicin-resistant (Rif R ) E. coli were cultured and excretion of probiotics was studied using PCR on individual faecal and post-mortem samples, and from manure collected after the challenge with resistant E. coli . CTX R and Rif R E . coli isolates were characterized to detect transfer of the bla CTX−M-1 to other strains. . Overall, there was no significant reduction in faecal excretion of CTX R and Rif R E. coli in IPro pigs compared with INT pigs, although the CTX R and Rif R E. coli titres were slightly, but significantly lower in the colon, caecum and rectum at post mortem. Excretion of the probiotics decreased with age, but Nissle 1917 was detected in most pigs at post-mortem. No transfer of the bla CTX−M-1 gene to probiotic and other E. coli strains was detected. In conclusion, in our experimental conditions, the used probiotics did not reduce shedding of the challenge strain.